2020
DOI: 10.1002/nbm.4430
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of interrater reliability of different muscle segmentation techniques in diffusion tensor imaging

Abstract: Muscle diffusion tensor imaging (mDTI) is a quantitative MRI technique that can provide information about muscular microstructure and integrity. Ultrasound and DTI studies have shown intramuscular differences, and therefore separation of different muscles for analysis is essential. The commonly used methods to assess DTI metrics in muscles are manual segmentation and tract-based analysis. Recently methods such as volume-based tractography have been applied to optimize muscle architecture estimation, but can al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 41 publications
5
22
0
Order By: Relevance
“…A recently published study by our group showed higher accuracy of VBT compared to MSB in healthy thigh muscles [ 6 ]. In contrast to those findings, similar outcomes for both techniques were found in calf muscles.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recently published study by our group showed higher accuracy of VBT compared to MSB in healthy thigh muscles [ 6 ]. In contrast to those findings, similar outcomes for both techniques were found in calf muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were instructed to lie still in a feet-first supine position. The MRI protocol was similar to our previous study in thigh muscles and included proton density-weighted (PD), T2-weighted (T2w), diffusion-weighted imaging (DWI), and a Dixon fat-quantification sequence (mDixonquant) in an axial slice order from proximal to distal (total acquisition time 18 min) [ 6 ]. To avoid shimming artifacts due to the large field of view (FOV), the calf region was divided into two FOVs of 480 × 264 × 150 mm 3 along the z -axis (stacks).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations